In Situ Construct of Zn–In Alloy Layer by In(BF4)3 Additive to Stabilize Zn Anode and Realize Ultra-High Reversible Zinc–Air Batteries - Ruo-Bei Huang; Xiao-Jie Huang; Tai-Rui Wu; Yi-Hang Liu; Meng-Yin Wang; Wei-Wei Wang; Hua Zhang; Si-Yuan Ma; Jian-Feng Li; De-Yin Wu; Jing-Hua Tian; Zhong-Qun Tian (Journal of the American Chemical Society, 2026)
Abstract Aqueous zinc–air battery (ZAB) is considered as a promising long-term energy storage technology due to its low cost, high safety, and high theoretical energy density. However, the zinc (Zn) anode suffers from issues such as dendrite growth, hydrogen evolution reaction (HER), corrosion, passivation, and volume deformation during cycling. To enhance the interfacial stability and deposition/dissolution behavior of the Zn anode, this work introduces indium tetrafluoroborate (In(BF4)3) into the electrolyte as a functional additive. The results demonstrate that the incorporation of indium (In) effectively regulates Zn nucleation behavior, promotes uniform Zn deposition, and significantly suppresses dendrite formation. Moreover, the dynamic alloy interface formed with In participates in reversible redox reactions that enable local defect self-healing, thus improving interfacial integrity and the compactness of the deposited structure. After modification, the ZAB achieves an ultralong cycle life of over 400 h under a current density of 5 mA cm–2 and 20 min per cycle, and ultrahigh reversibility for 320 h at current density of 2 mA cm–2 and 4 h per cycle under high depth of discharge/charge. The ZABs with In(BF4)3 additive exhibit reduced voltage polarization and excellent rate capability at various current densities, exhibiting enhanced cycling stability and electrochemical performance significantly. This work shows clearly the strategy of in situ constructing a Zn–In alloy layer by electrolyte engineering, which can guide the design and preparation of a stable Zn anode for not only ZABs but also the other Zn-based batteries.